FDI and productivity convergence in central and eastern Europe: an industry-level investigation - Martin Bijsterbosch; Marcin Kolasa (European Central Bank (ECB), 2009)
This paper presents empirical evidence of the effect of FDI inflows on productivity convergence in central and eastern Europe, using industry-level data. Four conclusions stand out. First, there is a strong convergence effect in productivity, both at the country and at the industry level. Second, FDI inflow plays an important role in accounting for productivity growth. Third, the impact of FDI on productivity critically depends on the absorptive capacity of recipient countries and industries. Fourth, there is important heterogeneity across countries, industries and time with respect to some of the main findings.
Keywords: C23; F21; O33; 330; absorptive capacity; FDI; Productivity convergence; Auslandsinvestition; Produktivität; Wirtschaftliche Konvergenz; Panel; EU-Mitgliedschaft